The Pathogenic Neisseria Use a Streamlined Set of Peptidoglycan Degradation Proteins for Peptidoglycan Remodeling, Recycling, and Toxic Fragment Release - Schaub, Ryan E.; Dillard, Joseph P. (Frontiers in Microbiology, 2019)
Neisseria gonorrhoeae and Neisseria meningitidis release peptidoglycan (PG) fragments from the cell as the bacteria grow. For N. gonorrhoeae these PG fragments are known to cause damage to human Fallopian tube tissue in organ culture that mimics the damage seen in patients with pelvic inflammatory disease. N. meningitidis also releases pro-inflammatory PG fragments, but in smaller amounts than those from N. gonorrhoeae. It is not yet known if PG fragment release contributes to the highly inflammatory conditions of meningitis and meningococcemia caused by N. meningitidis. Examination of the mechanisms of PG degradation and recycling identified proteins required for these processes. In comparison to the model organism E. coli, the pathogenic Neisseria have far fewer PG degradation proteins, and some of these proteins show differences in subcellular localization compared to their E. coli homologs. In particular, some N. gonorrhoeae PG degradation proteins were demonstrated to be in the outer membrane while their homologs in E. coli were found free in the periplasm or in the cytoplasm. The localization of two of these proteins was demonstrated to affect PG fragment release. Another major factor for PG fragment release is the allele of ampG. Gonococcal AmpG was found to be slightly defective compared to related PG fragment permeases, thus leading to increased release of PG. A number of additional PG-related factors affect other virulence functions in Neisseria. Endopeptidases and carboxypeptidases were found to be required for type IV pilus production and resistance to hydrogen peroxide. Also, deacetylation of PG was required for virulence of N. meningitidis as well as normal cell size. Overall, we describe the processes involved in PG degradation and recycling and how certain characteristics of these proteins influence the interactions of these pathogens with their host.